2020
DOI: 10.20473/jphrecode.v4i1.15954
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary Hygiene and Formaldehyde Content in Chicken Intestine in Traditional Markets of Jember Regency

Abstract: Latar Belakang: Bahan berbahaya masih sering ditemui pada berbagai macam makanan jajanan yang beredar di masyarakat. Usus ayam dapat diolah menjadi berbagai jenis masakan dan jajanan, seperti sate usus dan keripik usus. Tujuan: Tujuan penelitian ini adalah untuk menganalisa penerapan higine sanitasi proses produksi usus ayam dan identifikasi kandungan formalin. Metode: Metode penelitian ini adalah deskriptif observasional dengan pendekatan cross sectional. Wawancara dan observasi dilakukan pada responden untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…An international survey among consumers (Odeyemiet al, 2019) showed that food safety knowledge in the world, especially in developing countries like Africa, is still lower. In Indonesia, there was a lack of implementation in hygiene and food sanitation (Dakwani, 2019;Pratidina et al, 2017) (Moelyaningrum, 2019), (Dayanti, Moelyaningrum., & Ellyke, 2020). The respondents didn't realise that some foods consumed are likely to cause certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An international survey among consumers (Odeyemiet al, 2019) showed that food safety knowledge in the world, especially in developing countries like Africa, is still lower. In Indonesia, there was a lack of implementation in hygiene and food sanitation (Dakwani, 2019;Pratidina et al, 2017) (Moelyaningrum, 2019), (Dayanti, Moelyaningrum., & Ellyke, 2020). The respondents didn't realise that some foods consumed are likely to cause certain diseases.…”
Section: Introductionmentioning
confidence: 99%